2016
DOI: 10.1371/journal.pgen.1006484
|View full text |Cite|
|
Sign up to set email alerts
|

GW182-Free microRNA Silencing Complex Controls Post-transcriptional Gene Expression during Caenorhabditis elegans Embryogenesis

Abstract: MicroRNAs and Argonaute form the microRNA induced silencing complex or miRISC that recruits GW182, causing mRNA degradation and/or translational repression. Despite the clear conservation and molecular significance, it is unknown if miRISC-GW182 interaction is essential for gene silencing during animal development. Using Caenorhabditis elegans to explore this question, we examined the relationship and effect on gene silencing between the GW182 orthologs, AIN-1 and AIN-2, and the microRNA-specific Argonaute, AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 52 publications
4
28
0
Order By: Relevance
“…The expression of an endogenously kN-tagged phospholacking or phospho-mimicking S992 ALG-1 mutant form was as efficient as the kN-tagged wt ALG-1 to repress the reporter (Fig 7). These data, along with immunoprecipitation of ALG-1 mutants (Appendix Fig S5), confirm the capacity of both S992A and S992E ALG-1 mutants to interact with AIN-1/2 proteins, the C. elegans orthologs of GW182 that were shown to be essential to repress this tethering reporter in animals (Jannot et al, 2016). Taken together, these results support that the phosphorylation of S992 does not affect silencing efficiency of Argonaute bound to the 3 0 UTR of target mRNA.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…The expression of an endogenously kN-tagged phospholacking or phospho-mimicking S992 ALG-1 mutant form was as efficient as the kN-tagged wt ALG-1 to repress the reporter (Fig 7). These data, along with immunoprecipitation of ALG-1 mutants (Appendix Fig S5), confirm the capacity of both S992A and S992E ALG-1 mutants to interact with AIN-1/2 proteins, the C. elegans orthologs of GW182 that were shown to be essential to repress this tethering reporter in animals (Jannot et al, 2016). Taken together, these results support that the phosphorylation of S992 does not affect silencing efficiency of Argonaute bound to the 3 0 UTR of target mRNA.…”
supporting
confidence: 71%
“…MiRNA target sites are typically located on the 3 0 untranslated region (UTR) of target mRNAs and are only partially complementary to the miRNA (Bartel, 2009). Two specific tryptophan residues that are located in the N-terminal half of GW proteins directly bind into specific binding pockets on the surface of the PIWI domain of the Ago protein to form a stable complex (Schirle & MacRae, 2012;Pfaff et al, 2013;Jannot et al, 2016;Kuzuoglu-Ozturk et al, 2016). Two specific tryptophan residues that are located in the N-terminal half of GW proteins directly bind into specific binding pockets on the surface of the PIWI domain of the Ago protein to form a stable complex (Schirle & MacRae, 2012;Pfaff et al, 2013;Jannot et al, 2016;Kuzuoglu-Ozturk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noticed that 1351 miRNAs were from 12 Drosophila species, which accounted for about half of known insect miRNAs (Kozomara and Griffiths-Jones 2014). Many studies to elucidate the functions of miRNAs in regulating a variety of insect physiological processes have been carried out, such as in metamorphosis development (Sokol et al 2008;Gomez-Orte and Belles 2009;Ling et al 2014;Belles 2017;Wu et al 2017), cell growth (Wang et al 2010), behavior (Cohen et al 2017), sex determination (McJunkin and Ambros 2017), oogenesis , embryogenesis (Jannot et al 2016), immunity (Zhu et al 2013), insect-pathogen interactions (Hussain and Asgari 2010;Asgari 2013;Wu et al 2016), etc. Several miRNAs have been reported to regulate insect metamorphosis by targeting genes either in the ecdysone cascade or the JH cascade (Zhang et al 2009;Belles 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This study used a microarray-based approach, which unfortunately does not provide enough depth to fully understand miRNA function in a tissue-specific manner. In addition, this studies identified only a subset of miRNA targets, which rely on the scaffolding proteins AIN-1 and AIN-2, later found to be only present at specific developmental stages (Kudlow et al 2012; Jannot et al 2016).…”
Section: Introductionmentioning
confidence: 93%